2022
DOI: 10.1097/xcs.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Robotic Approach for Pancreaticoduodenectomy: A Propensity Score-Match Study

Abstract: BACKGROUND: Robotic surgery is a burgeoning minimally invasive approach to pancreaticoduodenectomy. This study was undertaken to compare survival after robotic vs “open” pancreaticoduodenectomy for ductal adenocarcinoma using propensity score–matched patients. STUDY DESIGN: With institutional review board approval, we prospectively followed 521 patients who underwent robotic (n = 311) or open (n = 210) pancreaticoduodenectomy. Patients who underwent rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Other multicenter RCTs, with the participation of surgeons who fulfilled the optimal learning curve, are still needed to compare the LPD and versus OPD in terms of cost-effectiveness, long-term survival, and disease-free survival. In the recent decade, robotic pancreatoduodenectomy (RPD) has gained attention and showed lower postoperative morbidity, shorter LOS, and higher survival relative to the OPD 65,70. Furthermore, RPD seems to be more beneficial relative to LPD in terms of lower conversion rate and transfusion rate 71.…”
Section: Discussionmentioning
confidence: 99%
“…Other multicenter RCTs, with the participation of surgeons who fulfilled the optimal learning curve, are still needed to compare the LPD and versus OPD in terms of cost-effectiveness, long-term survival, and disease-free survival. In the recent decade, robotic pancreatoduodenectomy (RPD) has gained attention and showed lower postoperative morbidity, shorter LOS, and higher survival relative to the OPD 65,70. Furthermore, RPD seems to be more beneficial relative to LPD in terms of lower conversion rate and transfusion rate 71.…”
Section: Discussionmentioning
confidence: 99%
“…A bold conclusion in a recent paper by Rosemurgy et al (8) thus warrants scrutiny. The authors present a major survival difference between patients having robotic and open pancreatoduodenectomy for pancreatic cancer, with 37 vs. 24 months survival favouring those who underwent robotic surgery.…”
mentioning
confidence: 93%
“…With the abovementioned considerations, we suggest that the perception of a superiority in the robotic approach in regards to survival should be tempered, if not avoided altogether, as there are several methodological issues and limitations not accounted for in the study reported in JACS ( 8 ). The authors’ bold claim that “ …robotic pancreaticoduodenectomy provides salutary and survival benefits for reasons yet unknown ” is hence unsubstantiated.…”
mentioning
confidence: 99%
See 2 more Smart Citations